Gestión contable y tributaria del comercial El Agua cantón Montalvo en el año 2019 - Villacis Goyes, Maria Angélica (2021)
In this Case Study it is about the Accounting and Tax Management of the Commercial "EL AGUA", in which it has been elaborated in order to be able to contribute with practical knowledge that helps guide an idea in a global way, forging a tool effectively and efficiently with respect to the accounting area, which has been prepared based on the needs and information that this property has provided for its development. Subsequently, a diagnosis was made through an interview with the owner of the property, it was considered to carry out this case study using methods such as inductive, explorative and analytical to make direct observations to the business which allowed access to the Annexes that they make their Tax Declarations to the SRI, which allowed us to know their strengths, threats, weaknesses and opportunities that it presents in its accounting structure and what its tax failures have been. It is concluded that the Commercial needs to take the necessary measures to keep its records correctly that improve with respect to the accounting part in order to obtain greater benefits and comply with its obligations before the regulatory entities on time.